Phase transition in complex |ψ|4 theory - Bittner, Elmar; Janke, Wolfhard (Physical review letters, 2002)
Motivated by recent claims for rather unconventional first-order phase transitions in the two- and three-dimensional complex |ψ|4 theory in certain parameter ranges we performed Monte Carlo simulation studies of this model. From our results in two and three dimensions we can unambiguously conclude that there is no evidence for a first-order transition, provided the measure of field fluctuations is treated properly. The origin of the discrepancy is traced by comparative simulations reproducing the erroneous results and by a transfer-matrix study of the one-dimensional case.